Evaluating the renoprotective effectiveness of sodium-glucose co-transporter 2 inhibitor therapy in patients with chronic kidney disease: A prospective study - Karadžić-Ristanović Vidna; Gajić Selena; Bontić Ana; Pavlović Jelena; Kezić Aleksandra; Radovanović Jovana; Radović Milan (Vojnosanitetski Pregled)
Background/Aim. Chronic kidney disease (CKD) is a global health concern associated with increased cardio-vascular risks and premature mortality. Proteinuria is a key prognostic indicator for CKD outcome. Sodium-glucose cotransporter 2 (SGLT2) inhibitors show potential for reducing proteinuria and slowing CKD progression. The aim of the study was to determine the impact of SGLT2 inhibitor therapy on CKD patients by evaluating the changes in the level of serum creatinine (sCr), 24-hour (24h) urine protein (UP), estimated glomerular filtration rate (GFR), and blood pressure (BP). Methods. This prospective study monitored 79 patients with CKD on therapy with SGLT2 inhibitors, who were followed up for one year. Patients received an SGLT2 inhibitor (dapagliflozin) once daily (10 mg), and assessment of specific parameters was conducted at baseline, 6 months, and 1 year later during the therapy. The study evaluated the levels of sCr, 24h UP, GFR, systolic BP (BPs), diastolic BP (BPd), uric acid (UA), total cholesterol (TC), triglycerides (Tg), low-density lipoprotein (LDL) cholesterol, sodium (Na+), and potassium (K+). Results. Over the one-year follow-up, significant changes were seen in UA levels (5.36, 4.99, 4.94 mg/dL, respectively; p = 0.032), 24h UP (662.60, 574.11, 417.09 mg/dL, respectively; p = 0.028), as well as BPs (128.44, 125.64, 126.12 mmHg, respectively; p = 0.026). No significant variations were observed in GFR, BPd, sCr, TC, Tg, LDL, and K+ levels. Na+ levels displayed a notable decrease (148.21, 147.57, 146.41 mmol/L, respectively; p = 0.021). Conclusion. The study suggests a potential benefit of SGLT2 inhibitors in managing CKD.